Allocentric Emotional Affordances in HRI: The Multimodal Binding - Jordi Vallverdú; Gabriele Trovato; Lorenzo Jamone (Multimodal Technologies and Interaction, 2018)
The concept of affordance perception is one of the distinctive traits of human cognition; and its application to robots can dramatically improve the quality of human-robot interaction (HRI). In this paper we explore and discuss the idea of “emotional affordances„ by proposing a viable model for implementation into HRI; which considers allocentric and multimodal perception. We consider “2-ways„ affordances: perceived object triggering an emotion; and perceived human emotion expression triggering an action. In order to make the implementation generic; the proposed model includes a library that can be customised depending on the specific robot and application scenario. We present the AAA (Affordance-Appraisal-Arousal) model; which incorporates Plutchik’s Wheel of Emotions; and we outline some numerical examples of how it can be used in different scenarios.